Analysis of Handling Loading And Unloading Delays In Improving Operational Performance On Km Dharma Ferry VIII - I Dewa Gede Andika Kusuma Wibawa; Haerani Asri; Sulastriani R (International Journal of Science and Environment (IJSE), 2026)
Delays in the loading and unloading process are one of the operational problems that can disrupt shipping schedules, increase operational costs, and reduce the quality of maritime transportation services. This study aims to analyze the factors causing delays in loading and unloading and their impact on the operational performance of KM Dharma Ferry VIII. The study used a qualitative approach with a case study method. The research population included all parties involved in loading and unloading activities and ship operations, while the sample was determined by purposive sampling consisting of the Captain, First Officer, Stevedoring Workers (TKBM), and port operational officers. The research instruments were in the form of interview guidelines, observation sheets, and documentation. Data analysis used the interactive model of Miles, Huberman, and Saldaña through data reduction, data presentation, and drawing and verifying conclusions with the help of NVivo 12 software. The results showed that delays in loading and unloading were caused by internal ship factors, land-side factors, and external factors such as vehicle density, passenger density, limited operational area, and weather conditions. These delays resulted in disruptions to shipping schedules, increased operational costs, and decreased service quality. The research conclusion shows that improving coordination between parties, optimizing vehicle arrangements, utilizing digital systems, and conducting regular operational evaluations are effective strategies for reducing loading and unloading delays and improving ship operational performance.